Emotional Intelligence and Interpersonal skills Training as strategies for Fostering Psychological sense of Community among Teachers in Ogun State, Nigeria. - Oscar, Yomi Akindele -; Adesoye, Emmanuel O.; Adesina, Sekinat; Adariku, Edith Yengura (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
The more psychological sense of community a group of teachers achieves, the better surrounding for personal learning of students and effective cooperation amongst colleagues. Yet a lot of teachers still manifest low Psychological sense of community with attendant consequences of devolving relationships, conflict with significant others in the school, poor delivery of teaching to the student, and low sense of belonging to the school. This study examined the effects of emotional intelligence (EI) and Interpersonal skills (IS) training on teachers’ Psychological sense of community. The study adopted a pretest, posttest, control group quasi-experimental design with a 3x3x2 factorial matrix. One hundred and twenty-six secondary school teachers were randomly selected and randomly assigned to two treatment groups and a control group. Collective Teacher Efficacy instrument was used to put participants into groups while the Sense of Community Index-2 was used to collect pretest and posttest data. Findings revealed that the two treatment interventions have significant main effect on teachers’ Psychological sense of community. It also revealed a no three-way interaction effects of treatment, collective efficacy and gender. It was concluded that secondary school teachers who demonstrate low Psychological sense of community could be assisted to develop better attitudes to school activities and improved sense of belongings to the school through emotional intelligence and Interpersonal skills training programmes. Keywords: Psychological sense of Community; emotional intelligence training; Interpersonal skills training; Collective Efficacy.